Model Administrasi Keuangan SDIT Future Islamic School Pekanbaru - Rafifah Qanita; Lili Marzila; Indah Ramadhani; Deta Rehulina Sitepu (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study discusses the financial administration model of SD IT Future Islamic School. There are 5 discussions that will be examined in this article, namely: the first point is the source of school financial income in the form of funds from the government, funds from parents and funds from student activities, the second point is school financial administration planning, the third point, financial management is carried out in 3 ways, namely: financial planning, financial implementation, where every income and expenditure is recorded and accountable, The fourth point is financial responsibility and the last is an evaluation of the financial management of the IT Future Islamic School elementary school. This research provides knowledge about the importance of good and correct management so that school funds do not occur. If school finances are not handled and managed by the right people, the learning process at the school will not run smoothly. The purpose of this study is to determine the model and financial management system in the school. The method used in this article is a descriptive qualitative method, where data is collected based on observation, interviews and documentation.